Survival A Theological-Political Genealogy. - Stern, Adam Y. (Intellectual History of the Modern Age Ser., 2021)
In Survival, Adam Stern asks what texts and traditions have made survival a recognizable element of our current political vocabulary. Examining works by Hannah Arendt, Walter Benjamin, Franz Rosenzweig, and Sigmund Freud, Stern shows that survival belongs to a history of debates about the sovereignty and subjection of Christ's body.